PEMAHAMAN MAHASISWA TERHADAP MATA KULIAH ILMU KESEHATAN DAN GIZI DI STKIP MELAWI - Dyah Anggorowati, Kurnia; Susilawati, Indria (STKIP Melawi, 2024)
Abstract: The research is to determine the level of student understanding of the Health and Nutrition Science courses at STKIP Melawi. The method used in this research is quantitative in the form of a survey. The instrument of this research is a statement questionnaire that must be answered by respondents. The data analysis technique used is descriptive analysis with calculations using percentages. The results of this research were after distributing research questionnaires to 35 students who had taken Health and Nutrition Science courses with 12 statements. It can be explained that the average number of